Wedding Traditions and Community Kinship System in the Village of Saluassing, Mamasa Regency - Riska Widiarnita (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. The purpose of this study is to introduce to the public the hengenai tradition of wedding parties which are usually held by the community in Saluassing Village, Bambang District, Mamasa Regency, West Sulawesi Province. The method used in this study is to use a qualitative approach with an interview model. The results of this study indicate that in the midst of modern times there are still many areas that hold weddings in accordance with the habits of their ancestors, where this is a legacy that has been passed down from generation to generation. Preserving culture in the midst of globalization is not an easy thing considering that currently there is a very large influence from outside culture. But as a child of the nation who has a sense of love for the country. We, as generations, should continue to hold onto our ancestral deposit so that the characteristics of the area where we live are never lost. Keep upholding tradition and keep instilling in your self thet our culture must be preserved. Keywords: wedding party; tradition; heritage;